2006
DOI: 10.1128/iai.74.2.920-926.2006
|View full text |Cite
|
Sign up to set email alerts
|

HpaA Is Essential forHelicobacter pyloriColonization in Mice

Abstract: Infection with the human gastric pathogen Helicobacter pylori can give rise to chronic gastritis, peptic ulcer, and gastric cancer. All H. pylori strains express the surface-localized protein HpaA, a promising candidate for a vaccine against H. pylori infection. To study the physiological importance of HpaA, a mutation of the hpaA gene was introduced into a mouse-adapted H. pylori strain. To justify that the interruption of the hpaA gene did not cause any polar effects of downstream genes or was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 42 publications
0
58
0
1
Order By: Relevance
“…While conducting a survey of nickel-responsive genes, HP1512 (frpB4) was identified as a gene of interest. The presence of HP1512 in membrane preparations has been documented in studies specifically targeting H. pylori OMPs (3,6,14). Previous work characterizing the iron transport and storage genes of H. pylori 26695 demonstrated that while two of the frpB alleles, frpB1 (HP0876) and frpB2/3 (HP0915/0916), were iron responsive, frpB4 (HP1512) was not responsive to either the iron concentration or fur mutation (14,44).…”
Section: Discussionmentioning
confidence: 99%
“…While conducting a survey of nickel-responsive genes, HP1512 (frpB4) was identified as a gene of interest. The presence of HP1512 in membrane preparations has been documented in studies specifically targeting H. pylori OMPs (3,6,14). Previous work characterizing the iron transport and storage genes of H. pylori 26695 demonstrated that while two of the frpB alleles, frpB1 (HP0876) and frpB2/3 (HP0915/0916), were iron responsive, frpB4 (HP1512) was not responsive to either the iron concentration or fur mutation (14,44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no other bacterial species were detected, with the exception of the closely related H. acinonychis (13), which was detected by the glmM assay. Furthermore, both the glmM and the hpaA genes have been used in similar previous studies (21,22,46), previous phenotypic analyses of Ͼ300 clinical H. pylori isolates have shown that HpaA was expressed in all strains studied (A.-M. Svennerholm, unpublished results), and HpaA has also been shown to be required for colonization of mice (8). The two genes in combination should thus provide a reliable method for quantification of H. pylori genomes in any type of sample.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of genes previously shown to be compromised for colonization in the mouse model, when mutated and identified as colonization defective in our screen, include the urease genes (16,22,62), the nickel transporter nikA gene, the fur gene (10), the bacterial ferritin pfr gene (64), the ␤-1-4 galactosyl transferase gene (18), several chemotaxis genes (21,59), and the flagellar sheath-localized adhesin hpaA gene (11). A hallmark of H. pylori infection is infiltration of neutrophils that produce reactive oxygen and nitrogen species, exposing both the host and the bacteria to DNA and protein damage.…”
Section: Discussionmentioning
confidence: 99%